2009
DOI: 10.1002/jso.21405
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic casting‐type calcifications is not a prognostic factor in unifocal small invasive breast cancer: A population‐based retrospective cohort study

Abstract: Except for patients with crushed stone-like microcalcifications breast cancer survival was excellent, 87-95% after 15 years. Casting-type calcifications were not a statistically significant prognostic factor. Tumors with casting-type calcifications were more often of high grade, hormone receptor negative, and HER2 positive but this was not statistically significant either. However, microcalcifications may be more prevalent in tumors with extensive ductal cancer in situ (DCIS) containing multiple foci of invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 16 publications
5
18
1
Order By: Relevance
“…A subgroup of women within the study who presented with mammographic casting-type calcifications was found to have unexpectedly poor survival rates for this tumour-size category. Although this finding has been the subject of some debate in the literature (James et al , 2003; Evans et al , 2006; Mansson et al , 2009), other research groups have reported similar findings that support the work of Tabar et al (Thurfjell et al , 2001; Peacock et al , 2004). …”
supporting
confidence: 81%
“…A subgroup of women within the study who presented with mammographic casting-type calcifications was found to have unexpectedly poor survival rates for this tumour-size category. Although this finding has been the subject of some debate in the literature (James et al , 2003; Evans et al , 2006; Mansson et al , 2009), other research groups have reported similar findings that support the work of Tabar et al (Thurfjell et al , 2001; Peacock et al , 2004). …”
supporting
confidence: 81%
“…Several authors found an increased rate of deaths [1,6,12,13,19] with rate between 10 and 50%, others did not [10,20]. In our cohort only 15 of 99 lesions contained fine linear or fine-linear branching calcifications.…”
Section: Discussioncontrasting
confidence: 43%
“…Thurfjell et al (16) revealed that mammographic appearance presenting as casting or pleomorphic calcifications alone had a significantly worse prognosis than other types of mammographic appearance in small invasive breast cancer, which was confirmed by the later series studies (14,15). Conversely, there are certain studies doubting the ability of mammographic calcification to predict the survival outcomes of patients (2123). In the present study, the outcome of 409 breast cancer patients with or without calcification, who had received BCS and post-surgery adjuvant treatment, were retrospectively studied.…”
Section: Discussionmentioning
confidence: 99%